Simplify 5a−8c+b+3c−9a+6b

.(1 point)

1 answer

To simplify the expression \( 5a - 8c + b + 3c - 9a + 6b \), we can combine like terms.

  1. Combine the \( a \) terms: \[ 5a - 9a = -4a \]

  2. Combine the \( b \) terms: \[ b + 6b = 7b \]

  3. Combine the \( c \) terms: \[ -8c + 3c = -5c \]

Now, putting it all together, we have: \[ -4a + 7b - 5c \]

Thus, the simplified expression is: \[ -4a + 7b - 5c \]

Similar Questions
  1. simplifying square roots1) find volume of this prism? v=bwh b=√12" w=√6" h=√8" 2)simplify: √576 3)simplify: √400
    1. answers icon 3 answers
  2. Simplify 8a − 2a.Simplify 12e − 5f − 7e +3f. Simplify 9x + 3y − 6 − 5x + 4y −3. Simplify 9/11z − 4/11z. Simplify
    1. answers icon 4 answers
  3. simplifying square roots1) find volume of this prism? v=bwh b=√12" w=√6" h=√8" 2)simplify: √576 3)simplify: √400
    1. answers icon 3 answers
  4. So I need some help on these Graphing Square Root Functions Quiz questions.1. Simplify 2 over √5 2. Simplify -11√112 3.
    1. answers icon 1 answer
more similar questions